Reduced ethylene synthesis of mangoes under high CO2 atmosphere storage - Renar João Bender; Jeffrey Karl Brecht; Steven Alonzo Sargent (Acta Scientiarum: Agronomy, 2021)
. High CO2 atmospheres have been reported to be accountable for slower ripening processes of many fruit species. In modified or controlled atmosphere storage of mangoes (Mangifera indica L.) delayed ripening is attributed to the effects of CO2 on ethylene biosynthesis, which is reduced under CO2 concentrations beyond 10%. In the present work the objective was to determine if those elevated CO2 atmospheres on ethylene synthesis could be attributed to the action of CO2 upon ACC oxidase. Mature green or tree ripe `Tommy Atkins` mangoes were, in four experiments, held in a flow through system of either 10 or 25% CO2 mixed to 5% O2 or only air for 14 or 21 days at 5, 8 or 12°C. Mangoes in the 25% CO2 atmosphere did not produce detectable levels of ethylene, whereas under 10% CO2 the production rates were significantly suppressed at 5 or 8°C. However, 1-aminocyclopropane-1-carboxylic acid (ACC) concentrations in mango mesocarp tissue at retrieval from storage were similar to the air controls and ACC synthase activity was not completely inhibited. The direct effects of CO2 concentrations on ACC oxidase activity is to be considered the most important factor in inhibiting ethylene biosynthesis of mangoes under 25% CO2 atmospheres.